Design of ultrasonic synthetic aperture imaging systems based on a non-grid 2D sparse array - de Souza, Júlio Cesar Eduardo [UNESP]; Romero, Montserrat Parrilla; Higuti, Ricardo Tokio [UNESP]; Martínez-Graullera, Óscar (MDPI, 2021)
This work provides a guide to design ultrasonic synthetic aperture systems for non-grid two-dimensional sparse arrays such as spirals or annular segmented arrays. It presents an algorithm that identifies which elements have a more significant impact on the beampattern characteristics and uses this information to reduce the number of signals, the number of emitters and the number of parallel receiver channels involved in the beamforming process. Consequently, we can optimise the 3D synthetic aperture ultrasonic imaging system for a specific sparse array, reducing the computational cost, the hardware requirements and the system complexity. Simulations using a Fermat spiral array and experimental data based on an annular segmented array with 64 elements are used to assess this algorithm.
Keywords: Sparse array; Synthetic aperture imaging; Ultrasonic imaging